1997
DOI: 10.1055/s-0038-1665441
|View full text |Cite
|
Sign up to set email alerts
|

Presence of P2X1 Purinoceptors in Human Platelets and Megakaryoblastic Cell Lines

Abstract: SummaryHuman platelets are thought to possess at least two subtypes of purinoceptor, one of which, coupled to G-proteins, could be the P2Y1 receptor (Léon et al. 1997). However, it has been suggested that the unique rapid calcium influx induced by ADP in platelets could involve P2X1 ionotropic receptors (MacKenzie et al. 1996) and the aim of this study was thus to investigate the presence of P2X purinoceptors in platelets and megakaryoblastic cells. Using PCR experiments, we found P2X1 mRNA to be present in hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
79
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 94 publications
(87 citation statements)
references
References 19 publications
(23 reference statements)
8
79
0
Order By: Relevance
“…In the next year, Vial et al [105] confirmed these observations and reported the finding of P2X 1 messenger RNA in platelets by the polymerase chain reaction. The suggestion that ADP also acted at the P2X 1 receptor [106] was shown to be erroneous when it was found to be based on experiments in which the commercially available ATP used was contaminated by ADP [107].…”
Section: The P2x 1 Receptormentioning
confidence: 76%
“…In the next year, Vial et al [105] confirmed these observations and reported the finding of P2X 1 messenger RNA in platelets by the polymerase chain reaction. The suggestion that ADP also acted at the P2X 1 receptor [106] was shown to be erroneous when it was found to be based on experiments in which the commercially available ATP used was contaminated by ADP [107].…”
Section: The P2x 1 Receptormentioning
confidence: 76%
“…The third component of the platelet P2 receptors is P2X 1 , a ligand-gated cation channel responsible for a fast calcium entry induced by ATP [14,85]. Although unable to trigger platelet aggregation by itself, the P2X 1 receptor induces transient shape change [13] and participates in collagenand shear-induced aggregation [86][87][88].…”
Section: Receptormentioning
confidence: 99%
“…Thus, doubts still remain as to whether the P2Y 1 receptor may exist in different conformations, which could account for a differential coupling to the Gq or Gi alpha subunits of G proteins. Platelets also express the ionotropic P2X 1 receptor (24)(25)(26)(27)(28). Its role in ADPinduced platelet aggregation is unknown and seems to be discrete, although this receptor is responsible for a unique fast calcium entry into platelets (24,29).…”
mentioning
confidence: 99%